Coenzyme Q10 prevents oxidative stress and fibrosis in isoprenaline induced cardiac remodeling in aged rats - Anayt Ulla; Mustafe Khalid Mohamed; Biswajit Sikder; AFM Towheedur Rahman; Farzana Akther Sumi; Murad Hossain; Hasan Mahmud Reza; G. M. Sayedur Rahman; Md Ashraful Alam (BMC, 2017)
Abstract Background The objective of the present study aimed to investigate the effect of CoQ10 treatment on isoprenaline (ISO)-induced cardiac remodeling in rats. Methods Rats were divided into three groups namely Control group, ISO treated group and CoQ10 + ISO treated group, each consisting of 6 rats. The cardiac specific CK-MB, AST, ALT activity and other oxidative stress parameters were estimated in heart and kidneys. Additionally histological examination was also performed to visualize the inflammatory cells infiltration and fibrosis in both tissues. Results Administration of ISO resulted in an increase in the heart-to-body weight (HW/BW) ratio and an also increased the serum CK-MB, AST and ALT enzyme activity. Serum levels of lipid peroxidation products, and oxidative stress markers showed significant increase in ISO-treated rats. Histopathological examination of heart tissue revealed focal areas of endocardium degeneration, mononuclear cells infiltration, fibrous tissue deposition, and increased thickness of the myocardium of left ventricle. Similar degeneration was also found in kidneys. Treatment with CoQ10 (100 mg/kg) significantly improved the oxidative stresses in ISO treated rats. Moreover, CoQ10 treatment prevented inflammatory cells infiltration and reduced fibrosis in ISO administered rats. Conclusion In conclusion, our study provides evidence that CoQ10 may prevent the development of cardiac remodeling, and fibrosis in ISO administered rats.